The Semen Quantity and Quality of Two Fowl Strains Supplemented with Vitamin E (Î±âTocopherol) - Nataamijaya, AG; Soetisna, A; Rejeki, Sri (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
The study on semen quantity and quality of Kampung and Arab fowl under various levels of vitamin E supplementation was conducted, using 2x4 factorial Completely Randomized Design with 4 replicates.Â Analysis of variance followed by Duncan New Multiple Range Test were used to analyze the data.Â LevelsÂ of vitamin E given orally were 0 IU (control); 2 IU (t1); 4 IU (t2) and 8 IU (t3) per bird daily.Â The results showed that semen volume was not affected by genotype (Kampung: 0.26 Â± 0.05 ml Vs.Â Arab: 0.22 Â± 0.05 ml) while the vitamin E treatments significantly (P<0.05) affected the semen volume i.e. 0.16 Â± 0.06 ml (control); 0.27 Â± 0.04 ml (t1); 0.28 Â± 0.03 ml (t2) and 0.23 Â± 0.03 ml (t3).Â Semen viscosity was not affected by genotype, but was substantially affected by vitamin E treatments.Â The semen pH was not influenced by all treatments given, spermatozoa concentration of Kampung (1.80 Â± 0.39 billion/ml) was not significantly different with that of Arab (1.86 Â± 0.16 billion/ml).Â Vitamin E treatments resulted in different (P<0.05) spermatozoa concentration among control (1.50 Â± 0.16 billion/ml), t1 (1.98 Â± 0.14 billion/ml), t2 (2.01 Â± 0.09 billion/ml) and t3 (1.87 Â± 0.18 billion/ml).Â No significant different found on semen mass movement between Kampung and Arab, also among vitamin E treatments.Â The spermatozoa motility of Kampung and Arab was not statistically different, however vitamin E improved motility significantly (P<0.05); control (2.90 Â± 0.59); t1 (3.5 Â± 0.16); t2 (3.54 Â± 0.25) and t3 (3.44 Â± 0.48).Â Percentage of dead spermatozoa of Kampung and Arab were 18.24 Â± 1.98% and 17.35 Â± 2.74%, while vitamin E supplementation results were as follows 18.10 Â± 3.03% (control); 18.54 Â± 2.01% (t1); 17.72 Â± 1.47% (t2) and 16.82 Â± 2.87% (t3) no significant different was found.Â Percentage of abnormal spermatozoa of Kampung (4.35 Â± 0.80%) and Arab (4.64 Â± 0.87%) was not different statistically.Â Among the vitamin E treatments the results was as follows 4.31 Â± 1.40% (control); 4.75 Â± 0.69% (t1); 4.94 Â± 1.91% (t2) and 3.97 Â± 1.14% (t3).Â However, significant (P<0.05) interaction effects were found in Kampung males at treatment t2 (4 IU) and t3 (8 IU). (Animal Production 7(2): 67-73 (2005)Â Key Words: Kampung, Arab, Fowl, Semen, Vitamin E